Making Your Wishes Known: Who Completes an Advance Directive and Shares It With Their Health Care Team or Loved Ones?. (December 2019) - Inoue, Megumi; Ihara, Emily; Terrillion, Albert
Using Andersen's health behavioral model as a framework, this study examined factors associated with the completion of advance directives and the behavior of sharing them with one's family and health care providers. Data were from the 2014 United States of Aging Survey ( N = 1, 153; aged 60 or older), and multinomial logistic regression was used for analysis. We found that 73% of respondents had advance directives. However, 28% have not shared their advance directives with anyone. The sense of having completed a great deal of preparation for the future and the number of illnesses were found to be relevant to the behavior of sharing advance directives. Existing educational training and interventions can be expanded to increase public awareness and encourage people to share their completed advance directives with others. Policies mandating physicians to engage in advance directive conversations with patients during annual checkups might improve completion and sharing of advance directives.